1998
DOI: 10.1182/blood.v92.2.434.414k24_434_442
|View full text |Cite
|
Sign up to set email alerts
|

Role of GATA-1 in Proliferation and Differentiation of Definitive Erythroid and Megakaryocytic Cells In Vivo

Abstract: To elucidate the contributions of GATA-1 to definitive hematopoiesis in vivo, we have examined adult mice that were rendered genetically defective in GATA-1 synthesis (Takahashi et al, J Biol Chem272:12611, 1997). Because the GATA-1 gene is located on the X chromosome, which is randomly inactivated in every cell, heterozygous females can bear either an active wild-type or mutant (referred to asGATA-1.05) GATA-1 allele, consequently leading to variable anemic severity. These heterozygous mutant mice usually dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…NAC inhibited the induction of genes encoding transcription factors such as GATA1 and NF-E2 in response to Epo, which is consistent with previous observations in butyrateinduced K562 cells (Chenais et al, 2000). Because GATA1 and NF-E2 are essential for erythroid differentiation (Francastel et al, 1997;Igarashi et al, 1995;Pevny et al, 1991;Suwabe et al, 1998;Takahashi et al, 1998), ROS might induce differentiation via these transcription factors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…NAC inhibited the induction of genes encoding transcription factors such as GATA1 and NF-E2 in response to Epo, which is consistent with previous observations in butyrateinduced K562 cells (Chenais et al, 2000). Because GATA1 and NF-E2 are essential for erythroid differentiation (Francastel et al, 1997;Igarashi et al, 1995;Pevny et al, 1991;Suwabe et al, 1998;Takahashi et al, 1998), ROS might induce differentiation via these transcription factors.…”
Section: Discussionsupporting
confidence: 91%
“…1B) and coproporphyrinogen oxidase (data not shown). Gene expression of the transcription factors NF-E2 (composed of MafK and p45), EKLF, and GATA1, which are critical for b major -globin gene transcription and erythroid differentiation (Francastel et al, 1997;Igarashi et al, 1995;Nuez et al, 1995;Pevny et al, 1991;Suwabe et al, 1998;Takahashi et al, 1998), was also upregulated (Fig. 1CeF).…”
Section: Nac Inhibits Changes In Gene Expression During Erythroid Difmentioning
confidence: 99%
“…To date, not much is known about the factors involved in the final stages of megakaryocyte maturation and proplatelet formation. Two transcription factor knock-out mice, NF-E2 and GATA-1, have been described that were both severely thrombocytopenic (Shivdasani et al, 1995(Shivdasani et al, , 1997Lecine et al, 1998;Takahashi et al, 1998). NF-E2 knock-out mice have normal Tpo levels and normal numbers of…”
Section: Discussionmentioning
confidence: 99%
“…However, we have found that the Gata1 G1.05/X mice suffer from erythroid leukemias (Shimizu et al 2008). Although the Gata1 G1.05/X mice survive to adulthood, some of them present splenomegaly, anemia and thrombocytopenia that are indicative of leukemia (Takahashi et al 1998). We subsequently found that majority of the Gata1 G1.05/X mice suffer from erythroleukemia by 200 days after birth (Shimizu et al 2004a).…”
Section: Introductionmentioning
confidence: 87%
“…Due to random inactivation of the X-chromosome, heterozygous female (Gata1 G1.05/X ) mice harbor two types of hematopoietic progenitor cells: one is harboring active Gata1 and inactive Gata1 knockdown (G1.05) alleles, whereas the other harbors inactive Gata1 but active G1.05 alleles (Takahashi et al 1998). As the former progenitors produce hematopoietic cells enough to sustain mouse development, we have maintained the Gata1 knockdown allele through female Gata1 G1.05/X mice.…”
Section: Introductionmentioning
confidence: 99%